Sosialisasi Pengembangan Usaha Mikro, Kecil Dan Menengah Di Kelurahan Mijen, Kecamatan Mijen, Kota Semarang - Nurchayati Nurchayati; Agung Wibowo; Parju Parju; Suroto Suroto; Muchayatin Muchayatin; Setyobudi Setyobudi; CH Astra Nugraha (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
One of the economic forces that has been supporting the Indonesian economy and regional economic strength is the presence of micro, small and medium businesses (MSMEs). Micro, Small and Medium Enterprises (MSMEs) play an important role in Indonesia's development and economy. However, MSMEs have limited resources and their small business scale encourages MSME entrepreneurs to look for innovative and creative solutions. This is a profitable opportunity to improve and develop MSMEs that are more innovative and creative. One form that MSME players can take is by implementing simple transaction recording and utilizing digitalization. The aim of this service activity is that MSME entrepreneurs can apply simple accounting in financial management, be ethical in the use of social and digital media, open up insights to market their business online and strengthen themselves as entrepreneurs so that MSMEs grow and develop. This service method involves providing outreach to the Mijen Village community. This activity was carried out with high community enthusiasm and support from Regional Government policies and figures from Mijen Village, Mijen District, Semarang City. This community service activity can increase insight and skills, as well as encourage the community to improve MSMEs.